Research utilization competence of postgraduate nursing students: A cross-sectional study - Heikkilä, Asta (SAGE, 2025)
Previous studies of research utilization competence of master's level nursing students have mostly focused on evaluations after a single evidence-based practice course. In this study, research utilization is defined as the process of acquisition, critical reading, and implementation of research knowledge. The aim of the study was to analyze the research utilization competence of postgraduate nursing students at the beginning and end of master's degree studies in Finland. Data were collected online from two groups of students (n = 33 and n = 60) with the structured Competence in Research Utilization-2 instrument and analyzed statistically. The study was reported using the STROBE guidelines. The students’ attitudes towards research utilization were positive. Students’ knowledge of research utilization was excellent and their skills were good at the end of their studies; they were higher than at the beginningof their studies. The study suggests that theoretically oriented nursing science education, including studies on conducting research, strengthens the research utilization competence needed for evidence-based practice.